Olim multorum patronus et praesidium, nunc ecce cliens: The Death and Posthumous Eulogy of Prince John of the Lithuanian Dukes, Spring 1538 - Rowell, S. C. (Senoji Lietuvos literatūra, 2020)
When Bishop John of the Lithuanian Dukes was translated from Vilnius to Poznań in the spring of 1536 he was already seriously ill with malarial fever. The ceremonies involved with his official ingress to his new see in March 1537 were curtailed and he was active personally in diocesan affairs (the consistory court) only during the spring and summer months. Bishop John died from his illness, quartan fever, on 18 February 1538. This article describes the processes which took place in the three months following the bishop’s demise: the withdrawal of his court and most of his administration from Poznań, his Requiem Mass in his cathedral sung by the suffragan bishop, Adrian Źakowski O.P. and the transportation of his corpse for eventual burial in Vilnius Cathedral, which took place in May 1538. Meanwhile in Leipzig a Mazovian student, Stanisław Czarny Chrościeski composed an epicedion or funerary eulogy in honour of the deceased prelated, dedicated to the Captain General of Greater Poland, Andrzej Górka. This work in Latin prose and verse was published for the first time from a nineteenth-century transcript by the literary historian Ludwik Ćwikliński in 1900 and has gone unremarked by Church historians for more than a century. The sole surviving copy of the 1538 Valentin Schumann imprint is held in the Russian National Library in St Petersburg and is reproduced here with a Lithuanian prose translation. Alongside Chrościeski’s compositions are epigrams by other Leipzig acquaintances of our author, later stars of the Silesian Lutheran Parnassus, Johannes Gigas and Valentin Nitius, master of the local school. Chrościeski’s prose address to Górka is interesting for its conceit that it is not Stanislaw who seeks patronage but Prince John himself. Unfortunately neither this text nor the verse address to the Fates reveals details about the bishop’s life and the circumstances of his death but the references to John as a warrior appear to confirm the reception of the prince-bishop’s own propagated self-image, known from contemporary occasional Latin verse.
Keywords: John of the Lithuanian Dukes (1499-1538); bishop; Vilnius; Poznań; death; memory; epicedion; Stanisław Czarny Chrościeski (ca 1517- 1578)